Lipid peroxidation in cell death - Gaschler, Michael M. (Biochem Biophys Res Commun, 2017)
Disruption of redox homeostasis is a key phenotype of many pathological conditions. Though multiple oxidizing compounds such as hydrogen peroxide are widely recognized as mediators and inducers of oxidative stress, increasingly, attention is focused on the role of lipid hydroperoxides as critical mediators of death and disease. As the main component of cellular membranes, lipids have an indispensible role in maintaining the structural integrity of cells. Excessive oxidation of lipids alters the physical properties of cellular membranes and can cause covalent modification of proteins and nucleic acids. This review discusses the synthesis, toxicity, degradation, and detection of lipid peroxides in biological systems. Additionally, the role of lipid peroxidation is highlighted in disease and death, and strategies to control the accumulation of lipid peroxides are discussed.